Does speed kill? Lending booms and their consequences in Croatia - Kraft, Evan; Jankov, Ljubinko (Journal of Banking & Finance, 2005)
Recent research connects lending booms with increased risks of banking and currency crisis. Another strand of literature connects financial deepening with long-term growth. Together, these findings pose dilemmas for policymakers. In the case of Croatia, we find that rapid loan growth increased the probability of credit quality deterioration and stimulated current account and foreign debt problems. Conventional monetary tightening was not very effective, due to capital inflows. Unconventional measures such as capital controls also had limited effectiveness. We propose limiting negative impacts by pro-active monetary policy, more restrictive fiscal policy and increased capital requirements for fast-growing banks, rather than measures to prevent lending booms ex-ante.